Hierarchy of hair loss stigma: media portrayals of cancer, alopecia areata, and ringworm in Israeli newspapers - Daphna Yeshua-Katz; Shifra Shvarts; Dorit Segal-Engelchin (BMC, 2019)
Abstract Background Over 300,000 people in Israel cope with temporary or permanent hair loss (alopecia) that results from diseases and medical treatments. For women, hair loss can be a highly traumatic event that may lead to adverse psychosocial consequences and health outcomes. Nevertheless, this phenomenon has been mostly ignored by health professionals as it is primarily considered an aesthetic-rather than as a health-related issue. Only recently the Healthcare Basket Committee approved financial assistance for the purchase of wigs by patients coping with hair loss. Given the important role that the media plays in shaping health policies related to diagnoses, treatment and support services, the current study sought to enrich our understanding of how the media portrays disease-related hair-loss. Methods Using framing and agenda-setting theories, this study examined the media portrayals of hair loss associated with three diseases-cancer, alopecia areata, and ringworm, depicted in Israeli newspapers in 1994-2016. The sample consisted of 470 articles about the three diseases: 306 on cancer, 36 on AA, and 128 on ringworm. Results Textual and visual analysis revealed the ways media marginalize this physical flaw. Cancer was framed in medical terms, and patients were portrayed as older Israeli-born people whose hair loss was absent from their experience. Ringworm was framed as a fear-inducing disease; patients were portrayed as faceless, unidentified immigrants that coped with visible hair loss. Articles on AA provided the greatest focus on the patient's experience of hair loss, but patients were portrayed as young foreign people. Conclusions Our results revealed a hierarchy of stigmas against hair loss, in which the media coverage marginalized this experience. The omission of hair loss by the media may explain, at least in part, why health professionals often ignore the psychosocial needs of these patients. Health insurance funding of wigs is a helpful but nevertheless insufficient solution to coping with feminine hair loss. Our findings may encourage media leaders to conduct planned media interventions to increase awareness of clinicians and health policymakers about the unique challenges faced by women coping with hair loss and promote health policy-making aimed at the well-being of these women.